2007
DOI: 10.1161/strokeaha.106.479733
|View full text |Cite
|
Sign up to set email alerts
|

Are Circulating Endothelial-Derived and Platelet-Derived Microparticles a Pathogenic Factor in the Cisplatin-Induced Stroke?

Abstract: Background and Purpose-To evaluate whether cisplatin-induced stroke is mediated by vascular toxicity with release of prothrombotic endothelial and platelet-derived microparticles (MPs). Methods-Endothelialand prothrombotic (Annexin V ϩ ) circulating MPs were quantified by flow cytometry in 18 patients with cancer, before and 3 days after administration of cisplatin, and compared with 18 healthy controls. Thrombin-antithrombin complex and prothrombin fragments (F 1ϩ2 ) were measured as markers of the activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 10 publications
2
31
0
1
Order By: Relevance
“…[1][2][3][5][6][7] In agreement with all the referred authors, it is concluded that once a vascular event has occurred, discontinuation of cisplatinbased chemotherapy is mandatory. 8 In this case cisplatin was changed for carboplatin.…”
Section: Vertebral Artery Occlusion After Chemotherapymentioning
confidence: 65%
See 2 more Smart Citations
“…[1][2][3][5][6][7] In agreement with all the referred authors, it is concluded that once a vascular event has occurred, discontinuation of cisplatinbased chemotherapy is mandatory. 8 In this case cisplatin was changed for carboplatin.…”
Section: Vertebral Artery Occlusion After Chemotherapymentioning
confidence: 65%
“…Vascular events have been described as a rare complication in relation to anticancer drugs. 4 Specifically, some authors have reported events in relation to cisplatin, [1][2][3][5][6][7] as well as to the combination of cisplatin, etoposide, and bleomycin. 2,5,6 We have not found any other case in literature of occlusion of a big cerebral artery induced by chemotherapy.…”
Section: Vertebral Artery Occlusion After Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…3 The levels of circulating prothrombotic MPs were high, with 741 endothelial-derived MPs/L, and 2373 platelet-derived MPs/L, (compared with mean 460 and 1023 MPs/L in controls with cancer). High levels of thrombin-antithrombin complex (6.0 g/L, normal values 1.0 to 4.1 g/L) and fragments F 1ϩ2 of prothrombine (2.6 nmol/L, normal values 0.4 to 1.1 nmol/L) were found 3 days after the stroke.…”
Section: Responsementioning
confidence: 94%
“…2 We recently postulated a mechanism of direct endothelial cell lesion induced by cisplatin, with release of prothrombotic fragments of endothelial cell in the circulation, causing further platelet and coagulation activation. 3 We demonstrated that cisplatin induces in patients with cancer a rapid and brief decrease in the level of circulating endothelial or platelet-derived microparticles (MPs), followed by an increase of these MPs with successive cisplatin infusions. 3 These bimodal kinetics may be consecutive to a brief increase in MPs clearance by liver Kupfer cells activated by cisplatin, followed by a longer phase of procoagulant MP release due to endothelial cell death or apoptosis.…”
Section: Responsementioning
confidence: 99%